Smoke screen - Brown, Sandra (New York : Pocket Books, 2008)
When newswoman Britt Shelley wakes up to find herself in bed with Jay Burgess, a rising star detective in the Charleston PD, she remembers nothing of how she got there...or of how Jay wound up dead. A disgraced firefighter realizes that the newswoman, Jay's last sexual conquest, might be his only chance to get personal vindication -- and justice for the seven victims of a police station fire.
Keywords: Journalists -- Fiction; Murder -- Fiction; Fire fighters -- Fiction